(untitled) (Fiep Bulletin - online, 2013)
The skin cancer had a substantial increase in the world in recent three decades. The excessive exposure to the sun and the reduction of the ozone layer are some of the main factors to that. Some classes of workers that are exposed to ultraviolet rays without the use of solar protection may be affected by this pathology when there is no knowledge about the evils that ultraviolet rays can bring. This study has as objective to verify the degree of knowledge, as well as the adoption of preventive measures on skin cancer by officials of the employees of Postal and Telegraph Brazilian Company that work in function of postman. This is a descriptive, transversal, quantitative study of which 270 postmen have agreed to participate and replied to a form containing objective questions which were used as variables. After compiled, the data were presented in tables and graphs with simple frequency and expressed in figures and percentages. The ethical aspects have been respected in accordance with the Resolution 196/96 (CNS-MS). The results show that 62.96% work as postman for more than five years; 91.85% are exposed to the sun daily from 10:00 h to 15:00 h, 76.30% for approximately 7 hours per day; 100% reported the supply of sunscreen by the company, of which, 76.30% use it once a day. The results suggest that the postmen know about the importance of the use of sunscreen in the prevention of skin cancer but nevertheless many of them believe that by using the sunscreen once a day, they are already protected and those who do not use the sunscreen are aware of the risks and do not blame the company of lack of incentive.